Construction of the Meaning of Radicalism and Efforts to Prevent the Spread of Radicalism (Study at Al-Azhar Senior High School Medan) - Dalimunthe, Ricky Shahriza Ramadhan; Badaruddin, Badaruddin; Achmad, Nurman (Budapest International Research and Critics University, 2021)
This study aims to determine the Construction of the Meaning of Radicalism and Efforts to Prevent the Spread of Radicalism in Al-Azhar Senior High School Medan. This type of research is qualitative research. The result shows that the teacher understands the concept of radicalism and understands that the concept of radicalism will have a negative impact on the personality of people affected by radicalism, the implementation of Pancasila values is carried out to students in the school environment as an effort to respond to radicalism. The Al-Azhar College School is not yet fully aware of the spread of radical understanding among students, so no special efforts are made to prevent the spread of radicalism, but the Al-Azhar College School already has a system that indirectly becomes an effort to prevent the spread of radicalism in Al-Azhar schools.